1985
DOI: 10.1557/proc-47-167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of W-N Alloys Formed By Sputter Deposition

Abstract: Thin films of W-N alloys have been prepared by reactive rf sputtering from a W target.Alloy compositions up to about 65at.%N can be achieved by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…The structure identi®cation indicated, as expected, the presence of the W 2 N fcc phase [10]. Due to nitrogen excess it is more correct to indicate this as a W 2 N 1 x phase, as proposed by Affolter et al [11]. The nitrogen excess should be responsible for the deviations observed in the interplanar distances, because by occupying the interstitials the nitrogen promotes lattice distortions.…”
Section: Tungsten Nitride Single Coatingssupporting
confidence: 57%
“…The structure identi®cation indicated, as expected, the presence of the W 2 N fcc phase [10]. Due to nitrogen excess it is more correct to indicate this as a W 2 N 1 x phase, as proposed by Affolter et al [11]. The nitrogen excess should be responsible for the deviations observed in the interplanar distances, because by occupying the interstitials the nitrogen promotes lattice distortions.…”
Section: Tungsten Nitride Single Coatingssupporting
confidence: 57%
“…The presence of the hexagonal ␦-WN phase only occurred in coatings containing more than 55 at.% of nitrogen and vestiges of other elements, e.g. oxygen (originated from the residual atmosphere in RF reactive magnetron sputtering studies [11,12], or purposely added to the reactive atmosphere in DC reactive magnetron studies [13]), or silicon [3].…”
Section: Chemical Composition and Structure At Room Temperaturementioning
confidence: 99%
“…1 -3 Depending on the nitrogen concentration, reactively sputtered W 1 ~ xNxcould be either amorphous or polycrystalline. 4 • 5 It has been found that amorphous W 1 ~ ,N x is a better diffusion barrier than the polycrystalline forms. 1 -3 · 6 Although this superior performance could not be positively attributed yet to the lack of grain boundaries of the amorphous form because the atomic composition changes together with structure, it is known that diffusion barriers often fail through grain boundary diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation temperatures between 450 ·c and 575 •c were chosen to be in the range of interest for diffusion barrier application, at the same time staying below the recrystallization temperature of the amorphous nitride which was determined to be around 620 ·c. 4 The kinetics of the oxidation process is derived from 2 MeV 4 He + backscattering spectra.…”
Section: Introductionmentioning
confidence: 99%